2021
DOI: 10.1136/bmjdrc-2021-002241
|View full text |Cite
|
Sign up to set email alerts
|

Two-year longitudinal trajectory patterns of albuminuria and subsequent rates of end-stage kidney disease and all-cause death: a nationwide cohort study of biopsy-proven diabetic kidney disease

Abstract: IntroductionData on the association between longitudinal trajectory patterns of albuminuria and subsequent end-stage kidney disease (ESKD) and all-cause mortality in diabetic kidney disease (DKD) are sparse.Research design and methodsDrawing on nationally representative data of 329 patients with biopsy-proven DKD and an estimated glomerular filtration rate above 30 mL/min/1.73 m2 at the time of biopsy, we used joint latent class mixed models to identify different 2-year trajectory patterns of urine albumin to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…16,21 Lower blood pressure levels have been shown to be associated with regression from moderate albuminuria to normal UACR, especially in patients with type-2 DM. 36 Optimizing hypertension management by lowering blood pressure levels reduce risk of progression from moderate albuminuria to severe albuminuria, and ESKD. 20 Hyperlipidemia has been implicated in the pathogenesis of DKD, however experimental models show that elevated levels of total cholesterol and triglycerides were not sufficient to drive overt changes in renal structure and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,21 Lower blood pressure levels have been shown to be associated with regression from moderate albuminuria to normal UACR, especially in patients with type-2 DM. 36 Optimizing hypertension management by lowering blood pressure levels reduce risk of progression from moderate albuminuria to severe albuminuria, and ESKD. 20 Hyperlipidemia has been implicated in the pathogenesis of DKD, however experimental models show that elevated levels of total cholesterol and triglycerides were not sufficient to drive overt changes in renal structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…16,21 Lower blood pressure levels have been shown to be associated with regression from moderate albuminuria to normal UACR, especially in patients with type-2 DM. 36 Optimizing hypertension management by lowering blood pressure levels reduce risk of progression from moderate albuminuria to severe albuminuria, and ESKD. 20…”
Section: Discussionmentioning
confidence: 99%
“…Recently, five different classes of DKD have been described based on cluster analysis of 6 variables [31]. These divergent phenotypes may have divergent pathogenesis and lncRNA trajectories [5]. Sixth, studies are largely based on glomerulocentric view of DKD pathogenesis, with glomerular hyperfiltration and protein leak viewed as the initial inciting event.…”
Section: Discussionmentioning
confidence: 99%
“…A broadening array of established and novel risk markers may be utilized for DKD diagnosis and staging; but clinical practice relies mainly on measurement of albuminuria, mainly urinary albumin/creatinine ratio (UACR), and estimated glomerular filtration rate (eGFR) [4]. However, the classical model of DKD starting with glomerular hyperfiltration and increased UACR, followed by declining eGFR has been greatly challenged; and many other different trajectories of albuminuria and renal function alteration were described in biopsy-proven DKD patients [5]. Moreover, DKD categorization by UACR is hampered by generally low sensitivity/specificity and significant intraindividual variability [6]; whereas creatinine-based eGFR formulas are perplexed by methodological limitations, nonrenal confounders, and inaccuracies at the near-normal range [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that microalbuminuria is not only an indicator of glomerular endothelial damage representing microvascular injuries but also reflects widespread vascular damage 11 . It is well established that microalbuminuria and macroalbuminuria were significant risk factors of CV and all‐cause mortality in diabetic patients 12–15 . The research of Hoorn Diabetes Care System cohort showed increased UACR (>3.0 mg/mmol) was prospectively associated with a higher risk of CV mortality in type 2 DM patients 16 .…”
Section: Introductionmentioning
confidence: 99%